Yield of three Commercial Watermelon Cultivars in Kenya as compared to a local landrace - Gichimu, Bernard M.; Owuor, B.O; Dida, M. M. (My University, 2010)
High yield is a major goal for watermelon (Citrullus lanatus) breeders. The objective of this study was to measure the yield potential of some watermelon accessions available in Kenya and identify high yielding ones for growers and for use in breeding programmes. A field trial was conducted at Maseno University Research Fields for two seasons between September 2007 and May 2008. Accessions studied included three most common commercial cultivars in Kenya, namely: ‘Sugarbaby’, ‘Crimson Sweet’ and ‘Charleston Gray’, one cultivar (‘Yellow Crimson’) newly introduced from the United States, and one local landrace (GBK-043014) from Kakamega district in Western Kenya. The experiment was laid out in a Randomized Complete Block Design with three replications. Data was collected on total number of female flowers per plant, main vine length, number of branches on the main vine, number and weight of fruits. Data collected were subjected to analysis of variance using SAS version 9.1 and significantly different means were separated using the Least Significant Difference test at P = 0.05. Linear regression was done to establish relationships between variables. Results revealed significant variation among accessions in all the yield components that were measured. The landrace had the highest yield compared to commercial cultivars owing to its long vine and extensive branching. It was therefore concluded that selection of desirable traits in this accession be given priority for future breeding programmes. ‘Yellow Crimson’ performed much better than other commercial cultivars and is therefore recommended to Kenyan growers as the cultivar with highest yield potential.
Keywords: Citrullus lanatus; Kenya; Watermelon commercial cultivars; Watermelon landraces; Yield potential